2013
DOI: 10.1111/phen.12027
|View full text |Cite
|
Sign up to set email alerts
|

Egg maturation dynamics of the parasitoid Microplitis rufiventris: starvation speeds maturation in early life

Abstract: The number of mature eggs carried by a female parasitoid at any given moment (egg load) is a fitness‐related parameter affecting reproductive potential and impacting upon host population dynamics. Microplitis rufiventris Kokujev (Hymenoptera: Braconidae) is a solitary koinobiont endoparasitoid wasp of several noctuid pests, including Spodoptera littoralis. The number of mature eggs carried by females at emergence is approximately 50. The rate of egg maturation is strongly affected both by feeding status and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Tauber et al (1986) and Danks (1987) reported that diapause may be defined as a genetically programmed, neurohormonally mediated, dynamic state of low metabolic activity during which morphogenesis ceases or significantly slows down. M. rufiventris is synovigenic parasitoid that do not have a full complement of egg load at eclosion and that continue to mature eggs throughout adult life (Hegazi et al, 2013). The egg load in reservoir region varied significantly among wasps of different DIs which was probably related to the resorption processes among old and or new produced mature eggs in wasp's diapausing for longer period and producing new mature eggs for wasp's diapause for short or long period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tauber et al (1986) and Danks (1987) reported that diapause may be defined as a genetically programmed, neurohormonally mediated, dynamic state of low metabolic activity during which morphogenesis ceases or significantly slows down. M. rufiventris is synovigenic parasitoid that do not have a full complement of egg load at eclosion and that continue to mature eggs throughout adult life (Hegazi et al, 2013). The egg load in reservoir region varied significantly among wasps of different DIs which was probably related to the resorption processes among old and or new produced mature eggs in wasp's diapausing for longer period and producing new mature eggs for wasp's diapause for short or long period.…”
Section: Discussionmentioning
confidence: 99%
“…Mature ovarian eggs were found in the calyx (323.3±6.3 μm, eggs to be laid first) and reservoir regions (389.1±20.6 μm, ready for transfer to the calyx region by involuntary unidirectional movement of eggs). Oocyte production was determined by dissecting the ovaries of each female and recording the number of mature oocytes (Hegazi et al, 2013) ranged 320-385 μm long. We recorded the egg load by counting the mature number of eggs in the ovarioles at emergence time and at 24h post-emergence.…”
Section: Link Of Diapause Intensity To Post-diapause Reproductive Sucmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information on the potential factors influ encing egg maturation dynamics of M. rufiventris wasp is lacking. Some effects on oviposition and feeding conditions are known (Hegazi et al 2013), but not the effects of a gradient of host availability. Knowledge of the oviposition-egg maturation behavior of M. ru fiventris may provide clues to designing efficient sys tems for rearing this parasitoid.…”
mentioning
confidence: 99%
“…This species is known as a biological control agent against Spodoptera frugiperda (Smith, 1797) (Coulson 1994). In the field, this parasitoid shows preference towards early larval instars (late first to early fourth) (Hegazi et al 2013). Some aspects of the reproductive biology of M. rufiventris were documented by Hegazi et al (2007).…”
mentioning
confidence: 99%